Formation and Electrochemical Properties of Nickel and Cobalt Transition Metals Oxide Films - I. A. Grekov; K. O. Yanushkevich; E. B. Chubenko; V. P. Bondarenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2022)
Films of cobalt oxide and nickel oxide on monocrystalline silicon substrates were obtained by electrochemical deposition from aqueous electrolyte solutions. Their structure and composition were studied by Raman microscopy and scanning electron microscopy. The results of the study by Raman spectroscopy showed that the obtained films are polycrystalline structures of cobalt (II, III) oxide and nickel (II) oxide, the crystalline perfection of which increases with an increase in the electrolyte temperature. It was found by scanning electron microscopy that nickel oxide films have a smoother surface, while cobalt oxide has a more developed structure consisting of lamellar crystals. The specific electrochemical capacity of cobalt oxide and nickel oxide films obtained under optimal conditions, measured by voltammetry, was 14.67 and 1634.08 F/g, respectively. The high specific electrochemical capacity of a nickel oxide film can be used to create efficient electrochemical devices and energy storage devices.